The obstacle race : the fortunes of women painters and their work. - Greer, Germaine, 1939- (Tauris Parke, 2001)
This text explains why there have been no female artists of the stature of Leonardo or Poussin by exploring the psychological, economic and political reasons for the virtually unchallenged patriarchalism of all western artistic establishments.